Specification for design and manufacture of water-tube steam generating plant ( including superheraters, reheaters and steel tube economizers ) - British Standards Institution (London BSI, 1985)
Steam boilers, Water-tube boilers, Boilers, Steam heaters, Heaters, Heating equipment, Steam plant, Steam engineering, Pressure vessels, Boilermaking, Valves, Steels, Boiler tubes, Design calculations, Stress, Thickness, Design, Stress analysis, Cylindrical shape, Flow nozzles, Dished ends, Holes, Reinforcement, Welding, Boiler stays, Test specimens, Inspection, Mechanical testing, Acceptance inspection, Defects, Non-destructive testing, Hydraulic tests, Pressure testing, Marking, Safety valves, Components, Pipes, Liquid-level indicators, Pipe connections, Pipe couplings, Bend couplings, Assembling, Dimensional tolerances, Repair, Acceptance (approval), Welded joints
Revised, Withdrawn
Cross References BS 10, BS 18, BS 21, BS 131:Part 2, BS 499, BS 639, BS 709, BS 759:Part 1, BS 759:Part 2, BS 806, BS 1134, BS 1501:Part 1, BS 1501:Part 2, BS 1501:Part 3, BS 1502, BS 1503, BS 1504, BS 1560:Part 2, BS 1640:Part 1, BS 1821, BS 2486, BS 1957, BS 1965:Part 1, BS 2600:Part 1, BS 2600:Part 2, BS 2633, BS 2910, BS 3059:Part 1, BS 3059:Part 2, BS 3500, BS 3601, BS 3602:Part 1, BS 3602:Part 2, BS 3604, BS 3605, BS 3636, BS 3688, BS 3799, BS 3889:Part 1, BS 3889:Part 2A, BS 3902, BS 3915, BS 3920, BS 3923:Part 1, BS 3923:Part 2, BS 3971, BS 4080, BS 4124:Part 1, BS 4204, BS 4504, BS 4570:Part 1, BS 4677, BS 4870:Part 1, BS 4871:Part 1, BS 4882, BS 4937, BS 5044, BS 5046, BS 5135, BS 5447, BS 5500, BS 5762, ASTM A 105, BS 5996, BS 6072, ASTM A 106, BS 6208, BS 6443, BS 6693:Part 2, BS 6759:Part 1, PD 6493, ASTM A 234, PD 6510, ASME Section VIII, ASTM A 182, ASTM A 312, ASTM SE 446, ASTM SE 186, ASTM A 335, ASTM E 125, Factories Act, 1961
Replaced By BS 1113:1989
Keywords: Water-tube boilers -- Standards